2015
DOI: 10.1161/circresaha.115.304457
|View full text |Cite
|
Sign up to set email alerts
|

Pi3kcb Links Hippo-YAP and PI3K-AKT Signaling Pathways to Promote Cardiomyocyte Proliferation and Survival

Abstract: Rationale YAP, the nuclear effector of Hippo signaling, regulates cellular growth and survival in multiple organs, including the heart, by interacting with TEAD sequence specific DNA-binding proteins. Recent studies showed that YAP stimulates cardiomyocyte proliferation and survival. However, the direct transcriptional targets through which YAP exerts its effects are poorly defined. Objective To identify direct YAP targets that mediate its’ mitogenic and anti-apoptotic effects in the heart. Methods and Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
251
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(260 citation statements)
references
References 31 publications
7
251
2
Order By: Relevance
“…Increased phosphorylation of STAT5 results in nuclear retention (48), and therefore interaction of pSTAT5 with YAP1 would be expected to result in nuclear retention of YAP1. Intriguingly, recent ChIP studies for YAP1 in a cardiomyocyte cell line indicated significant enrichment for STAT5-binding sites within the vicinity of YAP1-bound sites (49).…”
Section: Erbb2 (Supplementalmentioning
confidence: 98%
“…Increased phosphorylation of STAT5 results in nuclear retention (48), and therefore interaction of pSTAT5 with YAP1 would be expected to result in nuclear retention of YAP1. Intriguingly, recent ChIP studies for YAP1 in a cardiomyocyte cell line indicated significant enrichment for STAT5-binding sites within the vicinity of YAP1-bound sites (49).…”
Section: Erbb2 (Supplementalmentioning
confidence: 98%
“…Previous studies have suggested that YAP regulates components of the AKT pathway (i.e., PI3K, PTEN, and AKT) and that the Drosophila Hippo ortholog MST1 binds and inhibits AKT directly (26)(27)(28)(29). Increased YAP expression in human liver tumors is associated with high levels of p- AKT (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, liverspecific knockout of the Hippo pathway components MST1/2, SAV1, or NF2 induces the expansion of hepatic progenitor cells via YAP/TAZ activation and leads eventually to the development of liver cancer (HCC, cholangiocarcinoma [CC], or both) (22)(23)(24)(25). Despite its importance in tumorigenesis, the role of Hippo signaling in the metabolic dysregulation that precedes the development of liver cancer remains unclear.Previous studies have suggested that YAP regulates components of the AKT pathway (i.e., PI3K, PTEN, and AKT) and that the Drosophila Hippo ortholog MST1 binds and inhibits AKT directly (26)(27)(28)(29). Increased YAP expression in human liver tumors is associated with high levels of p- AKT (30,31).…”
mentioning
confidence: 99%
“…A significance threshold was set at the commonly used values of ±1.3. Activation of the PI3K/AKT pathway, which is known to promote both cardiomyocyte proliferation and survival (Figure 3(a)) [38], peaked at 12 h and subsided 24 h after A1-CM exposure (Figure 3(b)). Conversely, there was a significant reduction in the expression of genes associated with cellular differentiation, including bone morphogenetic protein (BMP) signalling ( Z  = −1.13) and TGF-β signalling ( Z  = −1.89) pathways [39].…”
Section: Resultsmentioning
confidence: 99%